1995
DOI: 10.3354/meps127269
|View full text |Cite
|
Sign up to set email alerts
|

Ferrioxamines B and E as iron sources for the marine diatom Phaeodactylum tricornutum

Abstract: The utihzalon of iron from the trihydroxamate-type siderophores fernoxamine B (FOB) and fernoxamine E (FOE) by the manne diatom Phaeodactylum trlcornutum was studied Cells grown under iron-hmiting conditions took u p iron faster from FOE and FOB than from Fe-EDTA and FeCI, Minimal iron uptake from the siderophores was observed for cells grown in media with sufficient iron The uptake of iron from FOB was inhibited by the ferrous ion chelator BPDS evidence that a reductive pathway is involved in the uptake mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 31 publications
3
76
2
Order By: Relevance
“…In bacteria, FhuD enables the direct transport of Fe(III)-hydroxymate chelates across the plasma membrane. The identification of a diatom-type FBP1 is consistent with kinetic measurements of siderophore uptake in P. tricornutum (37) and supports the presence of a coupled FBP1/FRE-dependent siderophore-based system for the destabilization and subsequent reduction of organically complexed Fe(III)-hydoxymates at the cell surface. Although standard assays (38) failed to detect the production of siderophores in P. tricornutum (data not shown), we discovered the genetic basis for Fe-uptake mechanisms that are a combination of classical eukaryotic components and those commonly found in bacteria but not usually present in eukaryotes.…”
Section: Resultssupporting
confidence: 62%
“…In bacteria, FhuD enables the direct transport of Fe(III)-hydroxymate chelates across the plasma membrane. The identification of a diatom-type FBP1 is consistent with kinetic measurements of siderophore uptake in P. tricornutum (37) and supports the presence of a coupled FBP1/FRE-dependent siderophore-based system for the destabilization and subsequent reduction of organically complexed Fe(III)-hydoxymates at the cell surface. Although standard assays (38) failed to detect the production of siderophores in P. tricornutum (data not shown), we discovered the genetic basis for Fe-uptake mechanisms that are a combination of classical eukaryotic components and those commonly found in bacteria but not usually present in eukaryotes.…”
Section: Resultssupporting
confidence: 62%
“…We have not conducted Fe reduction measurements in the presence of FeDFB because it adsorbs to the C 18 columns used to separate the 59 Fe(II)FZ 3 . Extracellular reduction of FeDFB and its role in Fe acquisition by diatoms is, however, relatively well documented (Allnutt and Bonner 1987a;Soria-Dengg and Horstmann 1995;Maldonado and Price 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Although DFOB is typically added under iron-replete conditions, it is clear that subpopulations of marine phytoplankton and heterotrophic bacteria are able to make use of Fe (III) bound to DFOB when added under iron deficient conditions (Soria-Dengg and Horstmann 1995;Granger and Price 1999;Maldonado and Price 1999). We have shown that marine Vibrio sp.…”
Section: Identification Of a Natural Desferrioxamine Siderophore Prodmentioning
confidence: 96%
“…However, evidence now exists for specific iron uptake mediated by DFOB in marine phytoplankton and heterotrophic bacteria (Soria-Dengg and Horstmann 1995;Granger and Price 1999;Maldonado and Price 1999). This iron uptake has been monitored for both laboratory cultures and field experiments using natural communities from the subarctic Pacific (including one coastal upwelling area), the Sargasso Sea, and the Gulf of Mexico.…”
Section: Identification Of a Natural Desferrioxamine Siderophore Prodmentioning
confidence: 99%